Tabu dan Mitos dalam Webtoon “Next Door Country” serta Pemanfaatannya dalam Pembelajaran Menulis BIPA 4 - Nurichsania, Nina Amalia; Pangesti, Fida (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
Exploring taboos and myths in the context of teaching Indonesian to foreigners will aid students in interacting more effectively when communicating with native speakers. Web comics (webtoons) can serve as an effective tool to understand them and achieve communicative competency, one of which is